Electron transport and oxidative phosphorylation (Henry Stewart Talks, 2025)
Electron Transport Chain, Oxidative Phosphorylation, Proton Gradient and ATP Synthase, Role of Oxygen as Electron Acceptor, Protein Complexes in Inner Mitochondria, Chemiosmosis and Proton Motive Force, Integration with Metabolism and Disease